PENGAWASAN PENJUALAN OBAT KERAS OLEH BADAN PENGAWAS OBAT DAN MAKANAN PEKANBARU BERDASARKAN UNDANG UNDANG NOMOR 36 TAHUN 2009 TENTANG KESEHATAN - Deo Andika Putra S; Rika Lestari; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Health is the most important thing needed by the human body. Efforts to improve the quality of life in the health sector is a business that is very extensive and thorough, these efforts include increasing public health both physical and non-physical in accordance with Law No. 36 Year 2009 on Health. Sales of the drug is essentially a very helpful community in curing the disease, because it facilitates the provision of drugs to facilitate the healing of illnesses suffered by someone either drug -free or drug sold by prescription given. However, drug sellers often sell drugs not in accordance with the applicable rules. For example, in memjual hard drugs on a person without a doctor's prescription and do not know the purpose of the use of hard drugs. Sales of these drugs can essentially harm the public because of indiscriminate use of hard drugs can pose a danger to people's self -defeating, because hard drugs are drugs in the purchase must be accompanied by a doctor's prescription Although there has been a rule that is sufficiently severe sanction the sale of hard drugs but still occurs in everyday life, of course it is devastating for the community.Keywords: Supervision, Sale Of Hard Drugs, Health